RESILIENCE OF CONVICTS OF CHILD PROTECTION CRIMES IN CLASS IIA METRO CORRECTIONAL INSTITUTION - Alfhandy Adma Negara; Mulyani Rahayu (Universitas Nusa Cendana, 2026)
This study aims to examine how inmates convicted of child protection crimes at the Class IIA Metro Correctional Institution develop resilience in facing strong social stigma. Using a qualitative descriptive approach, the findings show that resilience is not an inherent trait but a dynamic process shaped through emotion regulation, social support, and participation in correctional development programs. By referring to the resilience framework of Edith Grotberg (I Have, I Am, I Can) and the resilience factors proposed by Karen Reivich and Andrew Shatté, the study finds that emotion regulation and the ability to reach out are the most dominant factors in building resilience. In contrast, aspects such as causal analysis and empathy are less developed among inmates. Institutional support, nondiscriminatory treatment by correctional officers, and inclusive coaching programs play a significant role in strengthening inmates’ psychological resilience. These elements help inmates cope with stigma and support their personal development during incarceration. This study highlights the importance of a humanistic and equitable correctional approach in fostering resilience as a foundation for successful rehabilitation and social reintegration. Keywords: Resilience; Prisoners; Child Protection; Stigma; Correctional; Coaching; Emotion Regulation